2004
DOI: 10.7863/jum.2004.23.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Fetuses With Clubfeet Diagnosed by Prenatal Sonography

Abstract: Fetuses with an antenatal sonographic diagnosis of clubfoot often have other anomalies, aneuploidy, or both. The false-positive rate for diagnosis of clubfoot is higher for unilateral clubfoot than bilateral clubfoot. The rate of associated anomalies is higher with bilateral clubfoot than unilateral clubfoot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 8 publications
3
28
2
2
Order By: Relevance
“…11 Anyway, regarding the clubfoot, ultrasound have proven to be the most reliable method of prenatal diagnosis. 9,10,15,18,[20][21][22][23][24] The ability of achieving prenatal diagnosis of clubfoot have increased during the past two decades from about 25% to over 80%. Reports about the risk of false-positive prenatal diagnosis during pregnancy are diverse: the rate of false-positive prenatal diagnosis vary widely from 0 to 40% in isolated clubfoot.…”
Section: Discussionmentioning
confidence: 99%
“…11 Anyway, regarding the clubfoot, ultrasound have proven to be the most reliable method of prenatal diagnosis. 9,10,15,18,[20][21][22][23][24] The ability of achieving prenatal diagnosis of clubfoot have increased during the past two decades from about 25% to over 80%. Reports about the risk of false-positive prenatal diagnosis during pregnancy are diverse: the rate of false-positive prenatal diagnosis vary widely from 0 to 40% in isolated clubfoot.…”
Section: Discussionmentioning
confidence: 99%
“…33,36-38,44-46. On the other hand, external factors related to development were also considered 6,31,35 and the deformity appears not to develop before the 12 th week of gestation, pursuant to a fetal ultrasonographic study. 47 The consensus concerning the true genetic inheritance pattern has not yet been established, but a multifactorial polygenic inheritance pattern that can be influenced by external factors is suggested 48,49 , with incomplete dominance and variable penetrance. 35 …”
Section: Etiologymentioning
confidence: 99%
“…Several studies have reported on the accuracy of prenatally diagnosed clubfeet [2,5,6,7,8,9], but none have been able to correlate characteristics found on obstetric US to severity at birth. Recently, we described and retrospectively evaluated a novel sonographic severity classification [10].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to counsel patients is dependent upon the accuracy of the prenatal ultrasound (US). Historically, this has been problematic with regard to clubfoot, as the reported false US diagnosis rates range between 0 and 29% in the literature [3,4,5,6,7]. …”
Section: Introductionmentioning
confidence: 99%